Biofilm formation of methicillin-resistant coagulase negative staphylococci (MR-CoNS) isolated from community and hospital environments. - Rathanin Seng; Thawatchai Kitti; Rapee Thummeepak; Phattaraporn Kongthai; Udomluk Leungtongkam; Surat Wannalerdsakun; Sutthirat Sitthisak (PLoS ONE)
Methicillin-resistant coagulase negative staphylococci (MR-CoNS) are the major cause of infectious diseases because of their potential ability to form biofilm and colonize the community or hospital environments. This study was designed to investigate the biofilm producing ability, and the presence of mecA, icaAD, bap and fnbA genes in MR-CoNS isolates. The MR-CoNS used in this study were isolated from various samples of community environment and five wards of hospital environments, using mannitol salt agar (MSA) supplemented with 4 μg/ml of oxacillin. The specie level of Staphylococcus haemolyticus, Staphylococcus epidermidis, Staphylococcus hominis and Staphylococcus warneri was identified by specific primers of groESL (S. haemolyticus), rdr (S. epidermidis) and nuc (S. hominis and S. warneri). The remainder isolates were identified by tuf gene sequencing. Biofilm production was determined using Congo red agar (CRA) and Microtiter plate (MTP) assay. The mecA and biofilm associated genes (icaAD, fnbA and bap) were detected using PCR method. From the 558 samples from community and hospital environments, 292 MR-CoNS were isolated (41 from community environments, and 251 from hospital environments). S. haemolyticus (41.1%) and S. epidermidis (30.1%) were the predominant species in this study. Biofilm production was detected in 265 (90.7%) isolates by CRA, and 260 (88.6%) isolates were detected by MTP assay. The staphylococci isolates derived from hospital environments were more associated with biofilm production than the community-derived isolates. Overall, the icaAD and bap genes were detected in 74 (29.5%) and 14 (5.6%) of all isolates from hospital environments. When tested by MTP, the icaAD gene from hospital environment isolates was associated with biofilm biomass. No association was found between bap gene and biofilm formation. The MR-CoNS isolates obtained from community environments did not harbor the icaAD and bap genes. Conversely, fnbA gene presented in MR-CoNS isolated from both community and hospital environments. The high prevalence of biofilm producing MR-CoNS strains demonstrated in this study indicates the persisting ability in environments, and is useful in developing prevention strategies countering the spread of MR-CoNS.